1999
DOI: 10.1212/wnl.53.3.637
|View full text |Cite
|
Sign up to set email alerts
|

An aggressive familial amyloidotic polyneuropathy caused by a new variant transthyretin Lys 54

Abstract: Histologic examination of sural nerve of a 32-year-old man with an aggressive polyneuropathy associated with autonomic failure demonstrated amyloid deposition, and familial amyloidotic polyneuropathy (FAP) was diagnosed. Immunohistochemical staining showed transthyretin (TTR) staining of the amyloid deposits in nerve. Sequencing revealed G to A transition in the codon 54 causing TTR Lys 54. This is a new variant TTR associated with aggressive FAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 9 publications
4
20
2
1
Order By: Relevance
“…The second family with this mutation was from Costa Rica and exhibited severe motor, sensory and autonomic neuropathies, vitreous opacity, and cardiac failure [24]. As all reported patients died before the age of 40 years, the authors concluded that Glu54Lys causes severe FAP [23,24]. In line with previous findings, five of six affected members of the present family died before the age of 45 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The second family with this mutation was from Costa Rica and exhibited severe motor, sensory and autonomic neuropathies, vitreous opacity, and cardiac failure [24]. As all reported patients died before the age of 40 years, the authors concluded that Glu54Lys causes severe FAP [23,24]. In line with previous findings, five of six affected members of the present family died before the age of 45 years.…”
Section: Discussionsupporting
confidence: 89%
“…The Glu54Lys mutation was first described in a Japanese family who presented with early autonomic symptoms (constipation, diarrhea and vomiting as the prominent symptoms), vitreous opacity, and heart failure [23] ( Table 2). The second family with this mutation was from Costa Rica and exhibited severe motor, sensory and autonomic neuropathies, vitreous opacity, and cardiac failure [24].…”
Section: Discussionmentioning
confidence: 99%
“…While our research was in progress, a Japanese group described a case of an aggressive FAP in a 32-year-old male associated with autonomic failure and amyloid deposits that specifically stained with anti-TTR antibodies in histological preparations [Togashi et al, 1999]. The same mutation was identified on exon 3 with SSCP analysis followed by sequencing of the proband's genomic DNA and detection of the heterozygous band in the sequencing gel.…”
Section: Discussionmentioning
confidence: 93%
“…No detailed systemic pathological findings proven by autopsy identified FAP with TTR Glu54Lys. In this report, we present the clinical features and autopsy findings of the progressive form of FAP type 1 in a family with a rare substitution of the variant TTR gene Glu54Lys [5] and compared with the common type of FAP with TTRMet30 and the others. Free of amyloid in the kidney is the major manifestation in autopsy.…”
Section: Introductionmentioning
confidence: 99%